Gold nanoparticles in the diagnosis and treatment of ovarian and cervical cancers: a comprehensive understanding - Zhang, Senhui; Li, Tong; Jiang, Deshuo; Shi, Hengmei; Hou, Huyang; Fu, Ziyi; Shi, Xiaoyan (Frontiers in Oncology, 2025)
Cervical and ovarian cancers pose a significant global threat to women’s health. Despite substantial medical advances in recent decades, gynecological malignancies remain a leading cause of female mortality, constrained by factors such as multidrug resistance, treatment toxicity, asymptomatic presentation in early stages, and genetic heterogeneity. Gold nanoparticles (AuNPs), leveraging their exceptional biocompatibility and multifunctional capabilities, demonstrate considerable potential across diverse fields including bioimaging, liquid biopsy, photothermal therapy, and targeted chemotherapy, thereby advancing precision oncology. Accordingly, this review synthesizes and analyzes the emerging applications of AuNPs in gynecological tumors over the past five years. Moving beyond superficial descriptions of functional features often limited in previous reviews, it places greater emphasis on elucidating the intrinsic relationships and mechanisms between functions from the perspective of their physicochemical properties. It further highlights the critical importance of AuNPs for constructing integrated diagnostic and therapeutic platforms. Simultaneously, this review provides a balanced examination of the challenges hindering the clinical translation of AuNPs and offers insights and perspectives on addressing these issues. It is anticipated that AuNPs may evolve into highly effective diagnostic and therapeutic strategies in the future.